2021
DOI: 10.1063/4.0000059
|View full text |Cite
|
Sign up to set email alerts
|

Finite-element simulation of photoinduced strain dynamics in silicon thin plates

Abstract: In this paper, we investigate the femtosecond-optical-pulse-induced strain dynamics in relatively thin (100 nm) and thick (10 000 nm) silicon plates based on finite-element simulations. In the thin sample, almost spatially homogeneous excitation by the optical pulse predominantly generates a standing wave of the lowest-order acoustic resonance mode along the out-of-plane direction. At the same time, laterally propagating plate waves are emitted at the sample edge through the open edge deformation. Fourier tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
2
5
1
Order By: Relevance
“…39−41 Because of the homogeneous laser excitation, the even harmonics in a defect-free sample, which exhibit symmetric displacement profiles (Figures 1d and 1f) relative to the sample central layer, are forbidden. 39,41 However, different from these reports where only odd harmonics were observed, we observed both even and odd harmonics, suggesting that asymmetric stress is present in the sample. 42 The asymmetric stress may originate in the defective layers, which we will discuss later.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…39−41 Because of the homogeneous laser excitation, the even harmonics in a defect-free sample, which exhibit symmetric displacement profiles (Figures 1d and 1f) relative to the sample central layer, are forbidden. 39,41 However, different from these reports where only odd harmonics were observed, we observed both even and odd harmonics, suggesting that asymmetric stress is present in the sample. 42 The asymmetric stress may originate in the defective layers, which we will discuss later.…”
contrasting
confidence: 99%
“…We found that only odd harmonics are excited in the defect-free, homogeneously excited sample, in agreement with the previously study. 41 However, when a defect layer is present, as long as its location breaks the mirror symmetry with respect to the middle atomic layer, even harmonics would appear. Such defect that presents either inside the sample or at the surface (e.g., oxidized surface layers or stacking fault) can result in even harmonics detected sensitively by the ultrafast nanoscale imaging measurements.…”
mentioning
confidence: 99%
“…Recent studies further utilize the acoustic properties in nanostructures such as ultrathin plates, nanowires, semiconductor superlattice, semiconductor interface, and phononic crystal . For example, when an ultrathin semiconductor plate is irradiated by pulsed light with penetration depth much larger than the sample thickness, the sample is photoexcited almost uniformly along the out-of-plane direction [Figure (a)].…”
mentioning
confidence: 99%
“…3,4 As reported in the pioneering works in the 1980's, 5,6 photoexcitation of metals and semiconductors with ultrashort laser pulses can generate GHz-THz acoustic waves on picosecond time-scale at the materials' surface through sudden lattice heating (thermoelastic effect) and/or deformation potential induced by photocarriers. 4,5,7,8 Recent studies further utilize the acoustic properties in nanostructures such as ultrathin plates, 10 nanowires, 11 semiconductor superlattice, 9 semiconductor interface, 12 and phononic crystal. 13 For example, when an ultrathin semiconductor plate is irradiated by pulsed light with penetration depth much larger than the sample thickness, the sample is photoexcited almost uniformly along the out-of-plane direction [Figure 1(a)].…”
mentioning
confidence: 99%
See 1 more Smart Citation